2021
DOI: 10.1111/oik.08619
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional quality of giant kelp declines due to warming ocean temperatures

Abstract: Giant kelp Macrocystis pyrifera forms extensive forests on temperate reefs, providing habitat and food for a diversity of marine life. Kelp biomass varies in response to changing ocean temperatures, but physiological responses as reflected in the nutritional quality of kelp tissue are poorly understood. Over a 19-year period in southern California, we found that nutritional quality of giant kelp tissue declined; nitrogen content of giant kelp tissue declined by 18%, while carbon content proportionally increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 137 publications
1
14
0
Order By: Relevance
“…Because all of the contributions considered at least one explicit variable to quantify the nutritional quality of the resource, none of them falls within the cluster of 'undefined food quality' (in green). Five of the articles of the Special issue(Chouvelon et al 2022, Lowman et al 2022, Mathieu-Resuge et al 2022, Sentis et al 2022, van Deurs et al 2022) fall within the cluster aquatic ecosystem/ stoichiometry-lipids/trophodynamics-fitness, a proportion that mirrors well the actual predominance of those themes within the overall research (Fig.2c). Two more articles of this Special issue (LeGall et al 2022, Zaguri et al 2022) belong to the cluster linking the nutritional geometry to physiological aspects, which is current ranked second in term of contribution to the overall research.…”
mentioning
confidence: 78%
See 3 more Smart Citations
“…Because all of the contributions considered at least one explicit variable to quantify the nutritional quality of the resource, none of them falls within the cluster of 'undefined food quality' (in green). Five of the articles of the Special issue(Chouvelon et al 2022, Lowman et al 2022, Mathieu-Resuge et al 2022, Sentis et al 2022, van Deurs et al 2022) fall within the cluster aquatic ecosystem/ stoichiometry-lipids/trophodynamics-fitness, a proportion that mirrors well the actual predominance of those themes within the overall research (Fig.2c). Two more articles of this Special issue (LeGall et al 2022, Zaguri et al 2022) belong to the cluster linking the nutritional geometry to physiological aspects, which is current ranked second in term of contribution to the overall research.…”
mentioning
confidence: 78%
“…‐ As generally observed in ecosystem ecology, evolutionary questions are still too rarely explicitly tested in trophic ecology investigations. Despite a large array of studies have observed and discussed the evolutionary tenets at play behind the selection of consumers nutritional requirements (see for example Hudson et al 2022 in this issue), the inclusion of such research questions in the general understanding of ecosystem functioning remains limited.‐ Finally, Lowman et al (2022) illustrate that the potential nutritional quality of basal producers can be significantly altered by global warming. In the context or the current global changes and considering the multiple stressors organisms are exposed to, understanding the causes and the consequences of changes in basal resource quality in a multistressor context (concomitant changes in temperature, nutrient and water availability, presence of pollutants …) is an urgent need, as much in terms of prediction of future ecosystem trajectories as in terms of goods and services provision by nature for humanity.…”
Section: Current Status and Perspectives Of The Research On Nutrition...mentioning
confidence: 99%
See 2 more Smart Citations
“…The nutritional quality of wrack obviously plays a critical role in determining feeding choices in macroinvertebrate detritivores on beaches Duarte et al, 2010bDuarte et al, , 2011Duarte et al, , 2014Lowman et al, 2021), similar to mesograzers (macrofauna grazing on living macrophytes) in subtidal ecosystems (Duffy & Hay, 1991). The protein content of algae is considered a key trait in determining their nutritional quality as food sources (Cruz-Rivera & Hay, 2000), similar to the case for plant consumers in other systems (White, 1993), and appears selectively to influence feeding by detritivores on sandy beaches (e.g.…”
Section: Variablementioning
confidence: 99%